Cloning of partial glycoprotein B gene and molecular epidemiological studies of bovine herpes virus -1 isolates - CHANDRANAIK, B M; RATHNAMMA, D; PATIL, S S; RANGANATHA, S; KOVI, RAMESH C; AKHILA, D S; ISLOOR, SHRIKRISHNA; RENUKAPRASAD, C; PRABHUDAS, K (The Indian Journal of Animal Sciences, 2014)
The study describes genetic grouping and molecular epidemiology of bovine herpes virus-1 (BoHV-1) through cloning of partial glycoprotein B gene of BoHV-1 isolates, with special reference to isolates recovered from cattle breeding stations. Samples were collected from 212 animals (91 bulls and 121 female cattle). Avidin-biotin ELISA employed on serum samples found 74 animals as seropositive for BoHV-1. On inoculation of 212 semen/swab samples to MDBK cell line for virus isolation, samples of 4 seropositive and 5 seronegative animals yielded cytopathic changes characteristic of BoHV-1. Partial gB gene of these isolates were cloned in pGEM T vector, nucleotide sequences were deduced and phylogenetic tree was constructed. Sequence analysis grouped 5 of these isolates under BoHV-1.1 cluster having highest sequence identities with previously described Indian, European and Brazilian isolates of BoHV-1.1. The other 4 isolates were clustered as BoHV-1.2 subtypes having 100% sequence identity with European strain of BoHV-1.2. We found that, apparently healthy, seronegative animals can be sources of BoHV-1, attributable to the unique pathogenesis/ latency of BoHV-1. This finding necessitates mandatory culling of breeding animals which are positive either in antigen detection or by serology, especially in countries which do not practice vaccination but report high seroprevalance of BoHV-1.